Analysing child to parent violence (CPV) - María Silvia López Alonso (INFAD, 2019)
Violence has never been easy to define because of the common psychological and subjective connotations associated to it. In this sense, defining child to parent violence (CPV) presents many difficulties because it is bidirectional, it involves parents and minors, in a situation in which the bully is the minor and the victim is the parent or guardian. This study aims to provide an overview of CPV, obtaining the most accurate definition, listing profiles and variables, highlighting the importance of family intervention, and suggesting guidelines for early action and prevention.